2019
DOI: 10.1088/1555-6611/ab1001
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength switching and tuning of fiber lasers by using a modifiable intra-cavity filter based on a modal Michelson interferometer

Abstract: An experimental study of the switching and tuning of optical fiber ring lasers is presented. The laser wavelength switching and tuning are based on the modifiable wavelength dependent losses of a modal Michelson interferometer, which is composed by a bi-conical fiber taper spliced with a single-mode fiber piece. The wavelength dependent losses of the interferometer are inserted in a ring cavity laser to allow wavelength selection of laser wavelength peaks which induce preferences to generate laser emissions. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…By altering the interferometer geometrical dimensions, the switchable and tunable characteristics of the laser output can be controlled by adjusting the cavity losses, respectively. The maximum output wavelength number is 13, and the wavelength tuning by displacement- curvature can reach 2.3 nm mm −1 were observed under the condition of the OSNR values about 50 dB [10] . In 2022, Silva-Alvarado et al proposed a high stability wavelength switchable and tunable erbium-doped fiber laser by utilizing a Mach-Zehnder interferometer (MZI) to achieve single/dual emission operation by using the polarization controller to adjust the cavity losses [11] .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…By altering the interferometer geometrical dimensions, the switchable and tunable characteristics of the laser output can be controlled by adjusting the cavity losses, respectively. The maximum output wavelength number is 13, and the wavelength tuning by displacement- curvature can reach 2.3 nm mm −1 were observed under the condition of the OSNR values about 50 dB [10] . In 2022, Silva-Alvarado et al proposed a high stability wavelength switchable and tunable erbium-doped fiber laser by utilizing a Mach-Zehnder interferometer (MZI) to achieve single/dual emission operation by using the polarization controller to adjust the cavity losses [11] .…”
Section: Introductionmentioning
confidence: 92%
“…In recent years, multi-wavelength output lasers are often achieved with multi-wavelength filters. These filters usually consist of special structures to achieve interference effects, thus achieving multi-wavelength laser output, such as Michelson [9][10] , Mach-Zendel [11] , Fabry-Perot [12] , and Zagnac [13] interferometers. Mach-Zendel interferometer is one of the most used and widely used interferometers, and has been fabricated for gratings [14] , pull cones [15] , photonic crystal fibers [16] , multi-core fibers [17][18] , etc.…”
Section: Introductionmentioning
confidence: 99%
“…where I sm1 and I sm2 are the intensities of the super-modes. ∆ϕ is the phase difference and can be calculated by [5,15]:…”
Section: Mach-zehnder Super-mode Interferometer and Working Principlementioning
confidence: 99%
“…The most common is adding a wavelength-dependent filter within the laser cavity to modulate the cavity losses and induce emissions at wavelengths with minimal losses and considerable gain. These wavelengthdependent filters are often based on interferometric structures such as Michelson [4,5], Mach-Zehnder [6], Fabry-Perot [7], and Zagnac [8] interferometers. One of the most used and suitable for many applications interferometer is the Mach-Zehnder interferometer, it has been manufactured for example with gratings [9], tapers [10], photonic crystal fiber [11,12], twin-core fiber [13], and multi-core fiber [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Salceda-Delgado et al also demonstrated a wavelength-switchable EDFL based on a modifiable intracavity fiber. [19] For the designed fiber laser, the maximum number of wavelength peaks was 13, the maximum wavelength tuning was about 2.3 nm and the SNR was approximately 50 dB. Zhou et al reported a multiwavelength EDFL based on a tapered in-line Mach-Zehnder interferometer, in which switchable single, dual, triple, and quad-wavelength laser emissions were realized.…”
Section: Introductionmentioning
confidence: 99%